Trading Volume and Capital Gains Tax - Evidence from Selected Stock Markets with Different Characteristics - Gniadkowska-Szymańska, Agata; Gubareva, Mariya (Journal of Finance and Financial Law, 2022)
The purpose of the article/hypothesis: The goal of this paper is to investigate the relationship between capital gains tax paid by investors and the liquidity of the market, expressed by the trading volume. Methodology: In this study, the measure of market liquidity, expressed by the trading volume, has been proposed as a variable that may be influenced by taxes on capital gains. The article presents a new approach to the analysis of the liquidity of capital markets. Results of the research: Based on the data analysis, it was found that the higher the taxes on capital gains are paid by investors, the less likely they are to take their profits, and this is the situation on a highly developed market (the analysed US market). However, as it turns out from the results obtained, in the case of European countries representing stock markets after the systemic transformation, the higher the taxes on capital gains, the higher the share trading in these markets should be.